2013
DOI: 10.1038/cgt.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccine cocktail expressing genotype A and C HBV surface and consensus core antigens generates robust cytotoxic and antibody responses in mice and Rhesus macaques

Abstract: There are well over a quarter of a billion chronic hepatitis B virus (HBV) carriers across the globe. Most carriers are at high risk for development of liver cirrhosis and subsequent progression to hepatocellular carcinoma. It is therefore imperative to develop new approaches for immunotherapy against this infection. Antibodies and cytotoxic T cells to different HBV antigens are believed to be important for reducing viral load and clearing HBV-infected cells from the liver. Some of the major challenges facing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…The consensus sequence for the MERS-CoV S protein vaccine was generated after analysis of the S protein genomic sequences, which were deposited in the GenBank-NCBI (National Center for Biotechnology Information) database. In previous reports, it was described that such consensus immunogens can induce broad cellular and humoral immune responses against diverse virus strains/isolates (24)(25)(26)(27). Sequences from both clades A and B were included in the construct design.…”
Section: Synthetic Development Of a Mers-cov Dna Vaccinementioning
confidence: 99%
“…The consensus sequence for the MERS-CoV S protein vaccine was generated after analysis of the S protein genomic sequences, which were deposited in the GenBank-NCBI (National Center for Biotechnology Information) database. In previous reports, it was described that such consensus immunogens can induce broad cellular and humoral immune responses against diverse virus strains/isolates (24)(25)(26)(27). Sequences from both clades A and B were included in the construct design.…”
Section: Synthetic Development Of a Mers-cov Dna Vaccinementioning
confidence: 99%
“…Only low amounts of S-specific and no PreS1- and PreS2-specific IFN-γ-secreting PBMC were detected. In mice, strong S-specific [32], [33] and negligible PreS1/PreS2-specific [33] cellular responses have been described after immunization with DNA vaccines expressing non-secreted L proteins. The comparably high DNA doses applied in those studies (15 µg [33] or 100 µg DNA [32] for a ∼20 g mouse) as opposed to 333 µg DNA for a ∼20 kg pig used in our study might explain the different level of S-specific cellular immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…This technique consists of the rapid injection of a large volume of plasmid DNA into the tail vein, resulting in uptake of the DNA into the cytoplasm of liver cells [35], and has been widely used in recent years to deliver DNA and RNA for gene function, gene therapy and for establishment of disease animal models (reviewed in [47]). Although HTVI is a valid approach to deliver antigens directly into the liver, it has been recently shown that it does not constitute and effective vaccination strategy because it leads to defective CD8 + responses [48]. In contrast, this method has been used to show that immunization of mice with adenovirus vectors that encode for the well-established P. yoelii PE antigens Py CSP or Py CelTOS, followed by HTVI challenge with the same proteins as luciferase fusions results in significant reductions in the luciferase signal in the liver [49].…”
Section: Discussionmentioning
confidence: 99%